Future governance options for large-scale land acquisition in Cambodia: Impacts on tree cover and tiger landscapes. Issue 94 (April 2019) - Debonne, Niels; van Vliet, Jasper; Verburg, Peter
Highlights: In 2015, 32% of Cambodian large-scale land acquisitions is converted to plantation. We simulate the impact of different LSLA policies on LSLA underuse. Interventionist policies maximize tree cover and natural areas in Cambodia. Preventive policies result in less fragmentation of core natural areas. Future policies affect where and to what extent a tiger reintroduction is possible. Abstract: This paper investigates how large-scale land acquisitions (LSLAs) can be governed to avoid underuse and thereby spare room for other land claims, specifically nature conservation. LSLA underuse occurs when land in LSLAs is not converted to its intended use. Taking Cambodia as a case, we map converted and unconverted areas within LSLAs using remote sensing. We develop three scenarios of alternative LSLA policies until 2040, and use a land system change model to evaluate how governing the underuse of LSLAs affects overall land use. Specifically, we evaluate the impact of these policies on future tree cover, the size and spatial integrity of natural areas, and the potential these natural areas can offer to meet the conservation target of a successful tiger reintroduction. In 2015, only 32% of LSLA area was converted. Simulations suggest that both interventionist (reclaim unconverted areas) and preventive (avoid non-conversion) policies dramatically reduce underuse. Interventionist policies perform best in limiting tree cover loss and in preserving natural areas, but preventive measures lead to significantly less fragmentation. Noninterventionist policies (no enforced policies) make tiger reintroduction in the Eastern Plains impossible. Preventive policies with well-enforced protected areas succeed in creating the largest potential for tiger reintroduction. Our results suggest that Cambodia can reconcile LSLAs with tiger reintroduction in the Eastern Plains only when using preventive land use policies. In the absence of such policies, tiger survival in the Eastern Plains is unlikely and only the Cardamom or Virachey forest may offer such potential.